Radio echo sounding survey along the profile of the JARE-43 seismic exploration on the Mizuho Plateau, East Antarctica - Masamitsu Takada; Shigeru Toda; Daisuke Kamiya; Takeshi Matsushima; Hiroki Miyamachi (National Institute of Polar Research, 2003)
A seismic exploration was conducted in the austral summer of 2001-2002 by the 43rd Japanese Antarctic Research Expedition (JARE-43) on the Mizuho Plateau, East Antarctica. We carried out the radio echo sounding survey along the seismic line in order to estimate the distribution of bedrock altitude. This report describes the outline of the radio echo sounding survey and the obtained result.